The impact of COVID-19 infection on hip fracture 30-day mortality. (April 2022) - Fadulelmola, Ahmed; Gregory, Rob; Gordon, Gavin; Smith, Fiona; Jennings, Andrew
Introduction: A novel virus, SARS-CoV-2, has caused a fatal global pandemic which particularly affects the elderly and those with comorbidities. Hip fractures affect elderly populations, necessitate hospital admissions and place this group at particular risk from COVID-19 infection. This study investigates the effect of COVID-19 infection on 30-day hip fracture mortality. Method: Data related to 75 adult hip fractures admitted to two units during March and April 2020 were reviewed. The mean age was 83.5 years (range 65–98 years), and most (53, 70.7%) were women. The primary outcome measure was 30-day mortality associated with COVID-19 infection. Results: The COVID-19 infection rate was 26.7% (20 patients), with a significant difference in the 30-day mortality rate in the COVID-19-positive group (10/20, 50%) compared to the COVID-19-negative group (4/55, 7.3%), with mean time to death of 19.8 days (95% confidence interval: 17.0–22.5). The mean time from admission to surgery was 43.1 h and 38.3 h, in COVID-19-positive and COVID-19-negative groups, respectively. All COVID-19-positive patients had shown symptoms of fever and cough, and all 10 cases who died were hypoxic. Seven (35%) cases had radiological lung findings consistent of viral pneumonitis which resulted in mortality (70% of mortality). 30% ( n = 6) contracted the COVID-19 infection in the community, and 70% ( n = 14) developed symptoms after hospital admission. Conclusion: Hip fractures associated with COVID-19 infection have a high 30-day mortality. COVID-19 testing and chest X-ray for patients presenting with hip fractures help in early planning of high-risk surgeries and allow counselling of the patients and family using realistic prognosis.